Aplikasi Teori Carl R. Rogers dalam Kampus Merdeka untuk Mewujudkan Pendidikan yang Humanis di Perguruan Tinggi - A. Hari Witono; Arif Widodo (Departement of Mathematics Education, 2023)
This study aims to analyze how humanist education is manifested in the independent campus policy in tertiary institutions. This study uses library research methods. The research was conducted by tracing the results of previous studies related to the theory of humanism and the independent curriculum. Research sources were searched online by typing the keywords Car R. Roger, humanism, independent campus and independent curriculum on the Google Scholar search engine, ProQuest, Elsevier and other online scientific information providers. The results of the study show that the independent campus has a close relationship with the theory of humanism initiated by Carl R Roger. The concept of independent learning is in line with the theory of humanism which upholds freedom of learning, learning experience and students have the right to develop themselves according to their respective talents and abilities. The form of humanism in the independent curriculum is to give freedom to students to study 20 credits outside the study program. Some of the activities that can be converted into courses include internships, humanitarian projects, student exchanges, teaching assistance, research, entrepreneurship, independent projects and organizing social activities. Based on the findings of this study, it can be concluded that the independent campus policy in tertiary institutions has led to the realization of a humanist education.